Differences of the intensity increase of optical signals with fluorescein between Cherenkov-light and luminescence of water. (1st September 2022) - Yamamoto, Seiichi; Yabe, Takuya; Akagi, Takashi; Kataoka, Jun
Abstract: The imaging of the luminescence of water and Cherenkov-light with fluorescein during irradiation is a useful method to increase intensity; however, the magnitudes of the increase in intensity for Cherenkov-light and luminescence of water have been neither evaluated nor compared. Therefore, we measured the Cherenkov-light and luminescence of water with and without fluorescein during irradiation, and then we compared the magnitudes of the intensity increase with fluorescein. For 6  and 10 MV X-rays as well as 6 and 12 MeV electrons, the intensity of the Cherenkov-light images increased only 2 to 3 times with fluorescein water compared with that of water. Meanwhile, for 100 kV X-rays and 150 MeV protons, the intensity of the luminescence images increased more than 10 times with fluorescein water compared with that of water. The difference could probably be attributed to the difference in the light-emission mechanisms and coherency between Cherenkov-light and the luminescence of water.